Technology-based SMEs and the geography of knowledge sourcing : a systematic review of empirical evidence - Klangboonkrong, Yiarayong (Cranfield University, 2011)
Knowledge access is crucial for firms, especially those with resource constraints facing the rapid change in technology. This systematic review attempts to provide an understanding on how technology-based small and medium-sized enterprises (SMEs) source external knowledge. With the extant literature pointing to the spatial characteristics as the central theme, I identify four generic conditional dimensions that shape the overall geographical pattern of knowledge sourcing. The industrial knowledge base, the market, the local conditions, and the institutional environment influence from whom and where firms source knowledge. The empirical evidence leads to my contention that the conditional dimensions presented are far from being straightforward. Points of caution that should be incorporated when interpreting general patterns are discussed. The main argument is that further understanding of the geography of knowledge sourcing may start from generic external factors but contextual sensitivity and analytical interpretations are invariably essential. Further research opportunities call for more understanding on a) the relationship between private firms and the institutional environment, b) how an individual firm builds and develops own network, and c) how relational asset and different types of knowledge interact.
Keywords: Networks; Clusters; Spatial proximity; Innovation; Knowledge access; Systematic review